2020
DOI: 10.3390/biology9050089
|View full text |Cite
|
Sign up to set email alerts
|

Next-Generation Sequencing and MALDI Mass Spectrometry in the Study of Multiresistant Processed Meat Vancomycin-Resistant Enterococci (VRE)

Abstract: Vancomycin-resistant enterococci (VRE), due to their intrinsic resistance to various commonly used antibiotics and their malleable genome, make the treatment of infections caused by these bacteria less effective. The aims of this work were to characterize isolates of Enterococcus spp. that originated from processed meat, through phenotypic and genotypic techniques, as well as to detect putative antibiotic resistance biomarkers. The 19 VRE identified had high resistance to teicoplanin (89%), tetracycline (94%),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 65 publications
0
10
1
Order By: Relevance
“…In addition to food-producing animals, VRE and their resistance genes have been reported and detected in foods at retail (meat, vegetables, cheese, and milk) [ 74 , 75 , 76 , 77 ]. This is a cause for enormous concern since it favors the dissemination of antimicrobial resistance organisms, consequently reducing therapeutic options [ 78 ].…”
Section: Persistence Of Vre Strains In Portuguese Food Animals Anmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to food-producing animals, VRE and their resistance genes have been reported and detected in foods at retail (meat, vegetables, cheese, and milk) [ 74 , 75 , 76 , 77 ]. This is a cause for enormous concern since it favors the dissemination of antimicrobial resistance organisms, consequently reducing therapeutic options [ 78 ].…”
Section: Persistence Of Vre Strains In Portuguese Food Animals Anmentioning
confidence: 99%
“…This is a cause for enormous concern since it favors the dissemination of antimicrobial resistance organisms, consequently reducing therapeutic options [ 78 ]. In Portugal, only a few studies have reported the presence of VRE in food such as cheese, poultry carcasses, and processed meat [ 74 , 79 , 80 , 81 , 82 , 83 , 84 ].…”
Section: Persistence Of Vre Strains In Portuguese Food Animals Anmentioning
confidence: 99%
“…Interestingly, prior to the restriction on avoparcin use in 1997 [ 44 ], 8 studies reported the prevalence of VRE in companion animals, while 27 studies reported the prevalence of VRE in companion animals after the avoparcin ban. As seen in our analysis, the prevalence was gradually rising prior to the ban but continued to fluctuate after the avoparcin ban.…”
Section: Discussionmentioning
confidence: 99%
“…Another application of proteomics techniques is the precise and accurate identification of bacterial strains and is used additionally in microbiological studies. A relevant example is the differentiation of Enterococcus faecium from other bacterial species from processed meat samples [ 274 ].…”
Section: Proteomics Applications In Food Safetymentioning
confidence: 99%